Application of Kaizen Principles to a Large Cochlear Implant Practice: A Continuous Quality Improvement Initiative at Mayo Clinic. Issue 6 (July 2019) - Sladen, Douglas P.; Olund, Amy P.; Schmitt, Matthew; Benson, Barbara; DeJong, Melissa D.; Dowling, Brittany P.; Carlson, Matthew L.
Abstract : Objective: To remove barriers and improve access for patients seeking cochlear implantation. Study Design: Prospective quality improvement study at a large tertiary academic care center. Methods: A Kaizen quality improvement model was applied over the course of a year. Four weeklong meetings were used to identify areas for improvement and remediation. Data were collected at baseline, 90-days, and 1-year postcompletion of the project. Outcome measures included lead times, defined as the wait time between first contact with the clinic and the first appointment, and the wait time between surgery and activation, and cycle times defined as the total test time needed to determine cochlear implant candidacy, and total time needed to complete initial activation. The total inventory kept as clinic stock was also calculated Results: Kaizen team members collected data for each outcome measure. After the Kaizen principles were applied, the following outcomes were observed: median lead times between first contact with the clinic to candidacy testing, candidacy testing to surgery, and surgery to activation of the implant remained stable from baseline to 1-year follow-up. Median cycle time for candidacy testing decreased from 7.3 hours at baseline to 3.0 hours at 1-year follow-up. Cycle times for initial activation of the device did not change over time. The total inventory of clinic stock was reduced by 31%. Conclusions: Though outcomes for lead and cycle times varied, implementation of Kaizen principles was found to be an effective method for completing this quality improvement project at a large cochlear implant program overall. Level of Evidence: 3a Abstract : Supplemental Digital Content is available in the text